Music and Social Change in South Africa: Maskanda Past and Present. Kathryn Olsen. 2014. Philadelphia: Temple University Press. 10 tables, 18 figures, index, 222pp. - Amoros, Luis Gimenez (International Library of African Music, 2015)
pages: 214-217
Keywords: South Africa; African Music